Toward Quantum-Resilient PKI: A Systematic Literature Review of Post-Quantum Certificates Model - Nor Azeala Mohd Yusof; A H Azni; Farida Hazwani Mohd Ridzuan; Nur Hafiza Zakaria; Sakinah Ali Pitchay; Abdul Alif Zakaria; Tasnuva Ali (Usim Press, 2026)
Indexed by MyCite